Analisis Pemikiran Harald Motzki Tentang Hadis – Hadis Hukum: Metodologi Isnad Cum Matn dan Implikasinya Pada Studi Otorisitas Hadis: Analysis of Harald Motzki’s Thoughts on Legal Hadiths: Isnad Cum Matn Methodology and its Implications for the Study of the Authority of Hadith - M Faza Nahri (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2026)
The study of hadith in the discourse of modern Islamic studies is often caught between the polarity of traditionalism that accepts narrations without criticism and the radical skepticism of classical orientalists who doubt their historicity. This study aims to analyze the isnād-cum-matn analysis (ICMA) methodology developed by Harald Motzki in studying legal hadith and examine its implications for the authority of hadith in contemporary Islamic studies. The methodology used is qualitative research with a library research model and content analysis of Motzki's main works and other supporting literature. The results show that Motzki's approach offers a